Coagulation performance evaluation of alginate as a natural coagulant for the treatment of turbid water. Issue 1 (13th December 2021) - Saranya, Packiam; Ramesh, S. T.; Gandhimathi, R.
Abstract: Alginates are quite abundant in nature as they occur both as a structural component in marine brown algae (Phaeophyceae) comprising up to 40% of dry matter and as capsular polysaccharides in soil bacteria. Alginic acid is the only polysaccharide, which naturally contains carboxyl groups in each constituent residue, and possesses various abilities for functional materials. Experiments were carried out for water of turbidity 300 NTU. Alginate as such doesn't act as a coagulant, instead it should be converted to calcium alginate by adding calcium ions. Calcium chloride was used for imparting calcium ions necessary for the reaction. The dosage of calcium was fixed as 50 mg/L, 75 mg/L, 100 mg/L, 150 mg/L, 200 mg/L, and alginate doses between 2 to 10 mg/L. Calcium dosage below 50 mg/L was not sufficient for the formation of the egg-box structure which is responsible for the coagulation and flocculation process. For the mechanism of charge neutralization to take place effectively, calcium should be added first followed by alginate. pH and conductivity of the sample remain constant before and after the treatment. The dosage of alginate required for the treatment is less, so the cost of treatment also will be much less, thus alginate can replace the usage of chemical coagulants like alum. HIGHLIGHTS: Alginate, a natural and renewable bio-flocculant, produces no secondary pollution and hence can be used as potential coagulant for drinking water purposes. Unlike other coagulants, the pH and conductivity of the treated water do not change. The concentration of Ca ions is well within the desirable limit after treatment. Graphical Abstract